Nexus Among Carbon Dioxide Emissions, Gross Domestic Product, Average Years of Schooling on Life Expectancy at Birth in Indonesia - Wahyudi, Heru; Leny, Sandra Mei (International Journal of Energy Economics and Policy, 2025)
Indonesia faces a critical challenge in balancing economic growth with environmental sustainability and improving people’s welfare. As one of the countries with the largest carbon dioxide emissions in the world, increasing carbon emissions have negatively impacted environmental quality, health and life expectancy. This study aims to analyse the relationship between carbon dioxide emissions, gross domestic product and average years of schooling on life expectancy in Indonesia, with human development index (HDI) as a mediating variable. Using 12 years of data sourced from the Central Bureau of Statistics and the World Bank, this study applies a quantitative approach with Sobel test analysis to identify the direct and indirect effects of these variables through HDI. The results of the analysis show that carbon dioxide emissions have a significant negative impact on HDI, which in turn reduces life expectancy. In contrast, GDP and average years of schooling have a positive influence on HDI and life expectancy. However, the disparity in the distribution of GDP benefits and access to education between regions remains a major obstacle in improving human development equitably. This study confirms that HDI acts as an important mediator that strengthens the relationship between economic, social and environmental variables and life expectancy. The findings have significant policy implications, including the reduction of carbon emissions through sustainable strategies, increased investment in the education sector, and a more equitable redistribution of economic benefits. These evidence-based recommendations support the achievement of the sustainable development goals (SDGs) in Indonesia and make an important contribution to the development of scientific literature related to human development.